2019
DOI: 10.3390/nu11102371
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake of Green Nut Oil or DHA Ameliorates DHA Distribution in the Brain of a Mouse Model of Dementia Accompanied by Memory Recovery

Abstract: Docosahexaenoic acid (DHA), an omega-3 polyunsaturated fatty acid, has significant health benefits. Previous studies reported decreased levels of DHA and DHA-containing phosphatidylcholines in the brain of animals suffering from Alzheimer’s disease, the most common type of dementia; furthermore, DHA supplementation has been found to improve brain DHA levels and memory efficiency in dementia. Oil extracted from the seeds of Plukenetia volubilis (green nut oil; GNO) is also expected to have DHA like effects as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…Free DHA can incorporate into PCs and DHA-lysoPC of brain can be transformed into DHA-PCs by the action of lysoPC acyltransferase, and can improve the distribution levels of brain DHA-PCs in mice having dementia [35]. Therefore, our results of this study and previous reports suggest that GNO or DHA treatment could ameliorate the decreased distribution levels of brain DHA-PCs and improve memory function in dementia [10].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Free DHA can incorporate into PCs and DHA-lysoPC of brain can be transformed into DHA-PCs by the action of lysoPC acyltransferase, and can improve the distribution levels of brain DHA-PCs in mice having dementia [35]. Therefore, our results of this study and previous reports suggest that GNO or DHA treatment could ameliorate the decreased distribution levels of brain DHA-PCs and improve memory function in dementia [10].…”
Section: Discussionsupporting
confidence: 68%
“…In our recent study, we have reported that fourteen weeks supplementation of GNO or DHA improves memory function and DHA accumulation in the brain of SAMP8 mice [10]. Therefore, in this study, we treated SAMP8 mice by CO, GNO, and DHA for 14 weeks and their brains were analyzed using DESI-MSI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the five FFAs detected in our study, DHA had a distinct distribution in the epithelium of the vermilion (Figure 4), which made a remarkable difference between the vermilion and the skin. DHA is an important omega-3 PUFA in the human body and is well known for its multiple beneficiary effects [20,24,25]. In the vermilion, DHA may play a role as an antioxidant and thus contribute to the anti-aging of the lip.…”
Section: Discussionmentioning
confidence: 99%
“…The assignments of the fatty acids were based on the m/z values and their mass tolerances, previous lipid studies using DESI-MSI [16,17,20,21], as well as The Human Metabolome Database (http://www.hmdb.ca/spectra/ms/search) [37]. We defined the skin, epithelium of vermilion, and its underlying tissue areas on the ion image with reference to the H&E staining of the same section.…”
Section: Discussionmentioning
confidence: 99%